Access Denied in the Information Age
XIII, 239 p.
Keywords: We live in an information society. Or so we are told. Access to unlimited information will promote equality for all. But is the information society really going to be like this? Who is going to reap the rewards of new information and communication technologies? Focusing on a theme of exclusion, Access Denied in the Information Age dispels the myths of the information society. The authors here take a few steps back from the hype and consider the real place of these new technologies in society.